Development and characterization of arteether-loaded nanostructured lipid carriers for the treatment of malaria. (17th February 2016) - Ali, Zulfiqar; Mishra, Neeraj; Baldi, Ashish
Abstract : The purpose of the present work is to improve the antimalarial activity of the drug arteether (AE) by enhancing its solubility, by loading it into a nanostructured lipid carrier (NLC). The in vitro drug release profile of the NLC showed 93% drug release in 32 h. Complete eradication of the parasite from the blood and efficient anti-malarial pharmacological activity were observed, with the use of AE-loaded NLCs. These results suggest that nanolipid carriers of AE could be a promising carrier system to deliver the poorly soluble antimalarial drug through the oral route, by enhancing its solubility as well as preventing its degradation in the stomach.